The Effect of Mechanical Alloying on the Microhardness and Fracture Toughness of BaTiO3 - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2013)
t In this work, the effects of mechanical alloying on the mechanical properties of BaTiO3 were investigated. In order to examine the milling conditions and sintering parameters on the solid state formation of BaTiO3, X-ray diffraction technique was used. After mechanical alloying process, nanosized powder mixtures were produced. Sintering temperatures were 600, 700, 800, 900, 1000, and 1200 degrees C and sintering duration was 1 h. Besides X-ray diffraction examinations, mechanical properties of the BaTiO3 samples were determined by Vickers microhardness test. DOI: 10.12693/APhysPolA.123.188
Keywords: TITANATE; CERAMICS